VEIKSMŲ ATPAŽINIMAS KAIP VIRTUS DORMITIVA. - Dranseika, Vilius (Problems / Problemos, 2010)
In this paper, I propose the conceptual means that allow for the formulation of the claim that in the theories of philosophy of social science that take action recognition as the methodological basis of social explanation, action recognition is treated as a virtus dormitiva. Here action recognition may be understood either as a direct perception of action-types in behaviour or as an indeterminate holistic procedure of action interpretation. In both cases we encounter positing of nontransparent and further unexplainable epistemic power. The problem of virtus dormitiva becomes especially pressing if we recognize the methodological primacy of the problem of action recognition over the problem of action explanation.